BALANCED BOOTSTRAP ESTIMATORS FOR THE PROBABILITY OF MISCLASSIFICATIONS IN DISCRIMINANT ANALYSIS - MANGKU, I W. (School of Data Science, Mathematics and Informatics, IPB University, 2007)
In this paper we propose new error rate estimators based on balanced bootstrap technique, which are expected to per- form better than the existing estimators. These estimators can be computed by means of separate or mixture resampling methodol- ogy. We consider both of them.